Vegetation analysis of Samin watershed, Central Java as water and soil conservation efforts - MARIDI MARIDI; PUTRI AGUSTINA; ALANINDRA SAPUTRA (Biodiversitas Journal of Biological Diversity, 2014)
Maridi, Agustina P, Saputra A. 2014. Vegetation analysis of Samin watershed, Central Java as water and soil conservation efforts. Biodiversitas 15: 215-223. Samin watershed in Central Java is one of 282 Indonesian watersheds which are in critical condition.Nowadays, the sustainability of forest resources in the upstream of Samin watershed is threatened by exploitation of forest by people. Asa result, erosion and sedimentation are occurring in this area that may pose a threat of flooding and landslide. Therefore, we need seriousmeasures to maintain the function of Samin watershed, one of which is through the monitoring of vegetation in watershed. The purposeof this research was to analyze the structure and composition of vegetation in Samin watershed to support soil and water conservation.The survey of vegetation was conducted in 3 areas of Samin watershed based on geophysical conditions namely upstream, midstream,and downstream. At each sampling area, 37 sampling plots were randomly distributed in six observation stations. Vegetation analysiswas carried out in both the lower crop community (LCC) and the tree. Results showed that the number of LCC species found in theupstream, midstream, and downstream areas were 21, 34, and 28 respectively. The species diversity indexes of LCC vegetation in theupstream, midstream, and downstream areas were 1.04, 1.34, and 1.23 respectively. Based on this result, LCC vegetation in Saminwatershed was categorized in medium condition. The number of tree species found in the upstream, midstream, and downstream areaswere 27, 18, and 12 respectively. The species diversity indexes of tree vegetation in the upstream, midstream, and downstream areaswere 1.31, 1.15, and 0.97 respectively. Based on this result, the tree vegetation in Samin watershed was categorized in mediumcondition for the upstream and midstream areas, and low condition for the downstream area. Vegetation in Samin watershed must be preserved in order to maintain the sustainability of Samin watershed.